Symbolic anthropology and its relation with popular plastic art (مجلة إحالات, 2026)
The attempt to understand and interpret symbols requires, from the anthropological point of view, a study and analysis of the social structure and elements of culture and their interaction with the prevailing pattern ofsymbols, since it is society that gives symbols their meaning. For example, we find that in some societies that use what is often one of the forms of art, by decorating their bodies in ceremonial societies they use paints such as tattoos, skin stripes, jewellery and other artistic forms. Thus, the systematic and consistent interpretation of the pattern of symbols depends to a large degree on empirical research and the knowledge ofthe components of the culture.